PERAN ASEAN PLUS THREE MELALUI KOMITMEN ASEAN PLUS THREE EMERGENCY RICE RESERVE (APTERR) DALAM PENANGANAN ISU KETAHANAN PANGAN DI ASIA TENGGARA - Dewi Astuti Mudji (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2020)
The region of ASEAN is the leading producer of rice in the world. For most people in ASEAN member countries, rice is also a staple food commodity. ASEAN is disaster prone areas such as tsunami, landslide, earthquakes, floods and hurricanes causing degraded farmland, swallowing casualties as well as farm animals. The research having problem formulation, how the role of ASEAN Plus Three through the APTERR program, how the dynamics of food security issue. and how to implement APTERR's commitment as an effort to address food security issues in southeast Asia. The purpose of this research is to know the cooperation of ASEAN Plus Three through APTERR program. The Data obtained will be analyzed by descriptive method of analysis. .Based on the analysis of the data done, the conclusion that ASEAN is also a disaster prone areas such as tsunami, landslide, earthquakes, floods and hurricanes that cause farmland is damaged, swallowing casualties also livestock animals. As far as research analysis in the implementation of APTERR in the years 2015 – 2019, tier I and tier II programs have not been utilized. APTERR still focuses on tier III, which is giving direct assistance to victims of natural disasters.